STUDI KUALITAS EDIBLE FILM BERBASIS LIMBAH AIR CUCIAN BERAS (ORYZA SATIVA) DAN PEKTIN KULIT PEPAYA (CARICA PAPAYA L.) DENGAN PENAMBAHAN GLISEROL - Siti Asyiqah Azizah Ilham; Rahmaniah; Fitriyanti (JFT : Jurnal Fisika dan Terapannya, 2022)
The edible film is a thin layer that can be used as a food coating made from natural ingredients, which functions as a barrier to mass transfer such as moisture and oxygen. In minimizing environmental problems due to synthetic plastic waste, research was carried out on the manufacture of edible films from rice washing water waste (Oryza sativa) and papaya peel pectin (Carica papaya L.) with the addition of glycerol. This study aims to determine the quality of the mechanical properties and physical properties of edible films. The mechanical test includes the tensile strength test, elongation test, and absorption test for water resistance, while the physical test includes the FTIR test. In this study, the results of the tensile strength test on the sample met SNI 7818:2014. The results of the sample elongation test have complied with SNI 7818:2014 and JIS, 1975. The lowest water absorption was obtained in the sample with the addition of 5% glycerol. The FTIR results of the samples showed that there were no new functional groups and they still had distinctive groups in their pectin and CMC structures.